Pengaruh Kearifan Lokal terhadap Pendapatan Usahatani Padi Rawa Lebak di Desa Jejawi Kecamatan Jejawi Kabupaten Ogan Komering Ilir - Meindra Puja Kesuma; Laila Husin; Eka Mulyana (Agribusiness Study Program, Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2022)
The aims of this research were: 1) To find out kinds of local wisdom in Jejawi Village Jejawi Sub-District Ogan Komering Ilir Regency, 2) To find out the income of lowland swamp rice farmers in Jejawi Village Jejawi Sub-District Ogan Komering Ilir Regency, 3) To determine the effect of local wisdom on the income of lowland swamp rice farmers in Jejawi Village Jejawi Sub-District Ogan Komering Ilir Regency. The method used in this study was a survey method with 30 farmers as the samples. This research was conducted in March 2022. The sampling method used in this study was purposive sampling method. The data collected in this study were primary and secondary data. The research data was analyzed by using multiple linear regression analysis through SPSS. The result of the study showed that: 1) In Jejawi Village local wisdom was still applied in every process of rice farming steps starting from the preparation of land processing such as mengukut or cultivating together using a machete or hoe, seeding with menugal and melanting system planting by raising or mendederkan, fertilizing with natural humus, then maintaining with pest poisons which were made by themselves, harvesting by nyebat or ngarit and post-harvest by holding a thanksgiving. 2) The income earned by the lowland swamp rice farmers in Jejawi Village anually is Rp 777.716.668 with an average of Rp 25.923.888. 3) The variables that have positive effects include: land area, selling price, production cost have a negative effect on the income of lowland swamp rice farming in Jejawi Village. Kata kunci: local wisdom, lowland swamp, rice farming, income.